2017
DOI: 10.1038/npp.2017.56
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Control of Anxiety-Related Behaviors in Mice: Role of Inputs Arising from the Ventral Hippocampus to the Lateral Septum and Medial Prefrontal Cortex

Abstract: Anxiety is an adaptive response to potentially threatening situations. Exaggerated and uncontrolled anxiety responses become maladaptive and lead to anxiety disorders. Anxiety is shaped by a network of forebrain structures, including the hippocampus, septum, and prefrontal cortex. In particular, neural inputs arising from the ventral hippocampus (vHPC) to the lateral septum (LS) and medial prefrontal cortex (mPFC) are thought to serve as principal components of the anxiety circuit. However, the role of vHPC-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
166
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(180 citation statements)
references
References 56 publications
14
166
0
Order By: Relevance
“…The lateral septum receives dense 5-HT innervation and is particularly sensitive to SSRIs [60,61]. In PSD mice, chronic FLX and combination treatments but not exercise alone induced GABAergic FosB + cells, consistent with a chronic anxiolytic role for septal interneurons [62][63][64]. A Fig.…”
Section: Chronic Flx Reverses Stroke-induced Imbalance In Neuronal Acmentioning
confidence: 73%
“…The lateral septum receives dense 5-HT innervation and is particularly sensitive to SSRIs [60,61]. In PSD mice, chronic FLX and combination treatments but not exercise alone induced GABAergic FosB + cells, consistent with a chronic anxiolytic role for septal interneurons [62][63][64]. A Fig.…”
Section: Chronic Flx Reverses Stroke-induced Imbalance In Neuronal Acmentioning
confidence: 73%
“…However, this theta-rhythmicity may be more related to the approach or withdrawal that follows RA than it is to RA itself [46]. Conversely, a distinct population of ventral hippocampal cells that targets the lateral septum rather than the medial PFC inhibits anxiety-related behavior, perhaps as a form of negative feedback [44]. In contrast to the positive role of the basolateral, the basomedial amygdala appears to mediate suppression by the ventromedial PFC of a wide range of fear-and anxiety-related responses [47**].…”
Section: Subcortex-cortex Interactionsmentioning
confidence: 99%
“…Interestingly, the key output from the amygdala in its control of PAG-based RA behavior is ascending: to medial PFC either directly [41] or relayed [42] via the ventral hippocampus [43,44]. This transfer, like many other processes [45*], depends on theta-frequency synchrony [42].…”
Section: Subcortex-cortex Interactionsmentioning
confidence: 99%
“…Converging human and animal evidence suggests that the ventral hippocampus (HPC) (anterior HPC in humans) is critical for the expression of affective behaviors, particularly in the detection and resolution of approach–avoidance conflict, which evokes anxiogenic responses (Bach et al, 2014; Fanselow & Dong, ; Ito & Lee, ; O'Neil et al, ; Strange, Witter, Lein, & Moser, ). Much of this evidence comes from tasks that elicit approach–avoidance conflict without prior learning such as the elevated plus maze (EPM), light–dark box, and open field, which are commonly used in rodent studies as tests of anxiety and require the animal to respond based on an innate drive for exploration and an innate aversion to spaces that leave them open to predation (Bannerman et al, ; Kheirbek et al, ; Kjelstrup et al, ; Parfitt et al, ; Trivedi, ; Weeden, Roberts, Kamm, & Kesner, ). More recently, it has also been demonstrated that ventral HPC‐sensitive approach–avoidance conflict can also be elicited by presenting rodents with learned/conditioned stimuli that predict the availability of both positive and negative outcomes (Schumacher et al, ; Schumacher, Vlassov, & Ito, ), which may hold more translational value as real‐life approach–avoidance conflict scenarios usually involve learned stimuli (Ito & Lee, ).…”
Section: Introductionmentioning
confidence: 99%